Causes of ATtrition in CHIldren's NursinG (CATCHING): An exploratory mixed method study. (September 2018) - McKeever, Stephen; Whiting, Lisa; Anderson, David; Twycross, Alison
Abstract: Professional, financial and ethical reasons necessitate nursing improves its understanding of student attrition. Previous studies identify causes of attrition as multifactorial. However, few studies focus on children's nursing. This study aimed to explore causes of pre-registration children's nursing attrition. Exploring the causes of attrition was achieved through quantitative and qualitative approaches. Three years of quantitative data relating to attrition rates and causes was obtained. These data informed semi-structured interviews of children's nursing students, from four London universities. These students had faced challenges and either 'left' (n = 5) or 'stayed on' (n = 13) their pre-registration programme. Most attrition occurred in the first year of programmes and was primarily due to academic failure or personal circumstances; clinical placements also played a role. Emergent themes were 'expectations of pre-registration children's nursing' ; 'r ealities of a pre-registration children's nursing course', and 'factors that influence students leaving or staying on the course' . Many participants reported a reluctance to disclose issues while on their course. Support to continue on the programme was frequently obtained away from university and students described relying on self-determination to complete programmes. Findings indicated several areas of potential improvement for student support including targeted interventions focusing on a student's first year and reducing variation in support services provided. Highlights: Primarily children's student nurse attrition is due to personal or academic challenges. Support mechanisms are pivotal to students remaining on a programme of study. Personal tutors are a key element in proving support to students. Pre-course candidates require a realistic picture of children's nursing.